Analisis Kinerja Protokol Routing Dynamic MANET On-Demand (DYMO) dan Cluster Based Routing Protocol (CBRP) pada Mobile Ad-Hoc Network (MANET) - Muhammad Nurusshobah; Primantara Hari Trisnawan; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mobile Ad-Hoc Network (MANET) is a network technology that is composed of a collection of similar or different ad-hoc nodes that are connected using a wireless connection. MANET development is very likely to be applied to areas or conditions with minimal network infrastructure, such as disaster areas. Qualitative data analysis was performed on Dynamic MANET On-Demand (DYMO) and Cluster Based Routing Protocol (CBRP) performance by saving data from test results consisting of convergence, average throughput, average delay, average jitter, and package loss. From the results of the test analysis, the DYMO protocol has better results than the CBRP protocol based on the scheme of variations in the number of nodes. The average value of parameter throughput, average end to end delay, average jitter, and packet loss are 102.09 Kbps, 73.54 ms, 11.81 ms, and 1.79% respectively. In the wide variation scenario, DYMO is better seen from the average end to end delay, average jitter, and packet loss parameters with a value of 18.98 ms, 3.07 ms, and 0.35%. While the CBRP protocol is better of the average throughput with a value of 105.74 Kbps. In the data packet size variation scheme, the DYMO protocol is also known to be better seen from the average end to end delay, average jitter, and packet loss parameters with values of 32.86 ms, 8.44 ms, and 0.53%. While the CBRP protocol is better of the average throughput with a value of 104.86 Kbps. A better convergence value is obtained from the CBRP protocol with an average convergence time of 0.755375 seconds, but from the routing routing protocol level, the DYMO protocol is better than CBRP.